Causal factors of market demand affecting the growth and profitability of cannabis business - Kunnadilokkan, Kanapon; Laptaned, Ungul (Edelweiss Applied Science and Technology, 2025)
The cannabis business is emerging as one of the fastest-growing industries worldwide, driven by changes in legislation across various countries that have begun to permit the use of cannabis for both medical and recreational purposes. However, the industry continues to face several challenges, including the lack of stringent quality control, existing legal restrictions in many regions, and market regulatory uncertainties. The objectives of this research are: 1) to examine the causal factors influencing market demand, growth, and profitability in the cannabis business, 2) to analyze the influence of market demand’s causal factors on growth and profitability, and 3) to develop a causal model of market demand factors that impact the growth and profitability of the cannabis business. The researcher collected data through interviews and online questionnaires targeting cannabis entrepreneurs between February and March 2025, with a sample size of 400 respondents. The analysis results indicate that consumer accessibility significantly affects market demand, consumer accessibility influences growth and profitability through market demand, investment levels impact market demand, investment levels affect growth and profitability through market demand, and market demand itself directly affects growth and profitability. Based on these findings, cannabis entrepreneurs can better plan for business expansion and develop market-driven strategies focused on profitability and value creation while optimizing capital utilization to respond effectively to market demand.